Late cardiac tamponade after pacemaker implantation in patient with third degree atrio-ventricular block - a case report - Krasuska, Beata; Topyła, Weronika Sandra; Bal, Wioletta Anna; Bąk, Tomasz; Trojnar, Michał (Journal of Education, Health and Sport, 2017)
Patients suffering from third degree atrio-ventricular block need emergency treatment. Permanent cardiac pacing is the therapy of choice in third degree atrio-ventricular block. The incidence of complications following pacemaker implantation is low. The treatment is relatively safe. We present a case, which is an example of a very rare complication of cardiac pacing.